De Europese Commissie als motor van verandering.: Staatssteun, neoliberalisme en de sluiting van de Amsterdamse scheepswerven, 1976-1986. - Keulen, Sjoerd; Kroeze, Ronald (TSEG - The Low Countries Journal of Social and Economic History, 2021)
By analyzing the case of the closure of the Amsterdam shipyards in the 1980s, this article shows how the European Commission actively promoted a neoliberal turn in policies towards state support for economic sectors in Western-Europe. Besides the EC, the article also makes clear that quite early on leading civil servants within the Dutch ministries of Economic Affairs and of Finance embraced neoliberal ideas as an answer to tackle the economic crisis of the 1970s. A third, often neglected actor in explanations on the rise of neoliberalism were management consultants – in this case from management consultancy firm McKinsey – who wrote alarming reports about the shipbuilding industry and promoted ideas that emphasized the importance of business principles and individual managers as key for improvement, thereby offering an alternative to macroeconomic Keynesian models of growth.